Evaluation of the cytotoxicity of polyurethane and non-latex orthodontic chain elastics - Santos,R.L. (2012)
Allergy caused by latex proteins has been well documented. Thus, the study of non-latex materials, is necessary. The aim of this study is to evaluate the cytotoxicity of silver-coloured orthodontic chain elastics, of polyurethane and latex-free. Nine chain elastics from different manufactures (3 latex-free and 6 polyurethane) were divided into 9 groups of 10 elastics each: Group UK (Latex-free, 3M Unitek), Group TP (Látex-free, TP Orthodontics), Group AO (Látex-free, American Orthodontics), Group O (Polyurethane, OrthoSource), Group M (Polyurethane, Morelli), Group TD (Polyurethane, Tecnident), Group UD (Polyurethane, Uniden), Group AZ (Polyurethane, Abzil) and Group AK (Polyurethane, Aditek). The cytotoxicity essay was performed using cell cultures (L-929 line cells, mouse fibroblast) that were submitted to the cell viability test with neutral red ("dye-uptake") at 1, 2, 3, 7 and 28 days. Analysis of variance (ANOVA) with multiple comparisons and Tukey's test were employed (p<.05). The results showed no statistically significant differences between Groups UK, TP and AO in all experimental times (p>.05), except between the Groups UK and TP at 28 days (p<.05). There was significant statistically difference (p<.05) between the viability of the cells in the Groups O and TD with the Groups M, AZ, AK at 1 and 2 days. The polyurethane elastics showed lower cell viability in the first 48 hours, with increase on 3rd and 7th day, and viability similar to latex-free elastics at 28 days. It can be concluded that the latex-free chain elastic showed higher cell viability. The OrthoSource and Tecnident trademark showed lower cell viability the initial 48 hours.